Composite nanomaterial for inhibiting and degrading fungaltoxin as well as preparation method and application of composite nanomaterial

By combining polyphenols and metal salts to form composite nanomaterials with functionalized carbon quantum dots, the problem of incomplete degradation of fungal toxins in existing technologies has been solved, achieving highly efficient antibacterial and degradation capabilities, making it suitable for industrial applications.

CN121176473APending Publication Date: 2025-12-23INST OF AGRO FOOD SCI & TECH CHINESE ACADEMY OF AGRI SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511241664.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-12-23

AI Technical Summary

Technical Problem

Existing technologies for degrading mycotoxins suffer from problems such as incomplete degradation, poor environmental adaptability, and low cost-effectiveness. There is a lack of materials that combine broad-spectrum efficiency, environmental stability, and industrial feasibility.

Method used

A composite nanomaterial is formed by the self-assembly of polyphenolic components and metal salt components under specific conditions. Combined with functionalized carbon quantum dots, it achieves efficient antibacterial and fungal toxin degradation through coordination and redox capabilities.

Benefits of technology

It achieves a growth inhibition efficiency of over 95% against Aspergillus flavus, Aspergillus parasiticus, or Aspergillus ochraceus, and significantly degrades mycotoxins. The material has high stability, simple preparation, and low cost, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite nanomaterial for inhibiting and degrading fungaltoxin as well as a preparation method and application thereof, belongs to the technical field of biochemical engineering, and solves the technical problem that a degradable material with broad-spectrum high efficiency, environmental stability and industrial feasibility is lacked in the prior art. The preparation method of the composite nano material comprises the following steps: dissolving a polyphenol component and a metal salt component in a Tris-HCl buffer solution according to a molar ratio of 1: (1-3), controlling the pH value of the solution to be 4-6, stirring and reacting at 20-60 DEG C for 1-3 hours to obtain a self-assembly solution, dropwise adding an activated carbon quantum dot solution into the self-assembly solution, stirring in a dark place for 12-18 hours to obtain a reaction solution, and centrifuging the reaction solution to obtain a precipitate; washing the precipitate with water for 3-5 times, and drying to obtain the composite nano material. The composite nano material is used for inhibiting growth of aspergillus flavus, aspergillus parasiticus or aspergillus ochraceus and degrading fungaltoxin generated by the aspergillus flavus, the aspergillus parasiticus or the aspergillus ochraceus, and the antibacterial efficiency reaches 95% or above.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of bio-chemical engineering. More particularly, the present application relates to a composite nanomaterial for inhibiting and degrading mycotoxins, and a preparation method and application thereof. BACKGROUND

[0002] Mycotoxins (such as aflatoxin B1, ochratoxin A, etc.) pollution seriously threatens food safety and human health. Existing degradation technologies mainly include physical adsorption, chemical degradation, biological enzymatic degradation, and composite methods, which are as follows: 1) physical adsorption materials. Representative technology: activated carbon, modified montmorillonite, etc. through pore structure adsorption of toxins. Disadvantages: only transfer toxins without degradation, there is a risk of secondary release; 2) chemical oxidation degradation. Representative technology: ozone oxidation, hydrogen peroxide oxidation directly destroys the molecular structure of toxins. Disadvantages: strong oxidation conditions lead to loss of food nutrients, and residual chemical reagents may introduce new safety hazards. 3) biological enzyme degradation materials. Representative technology: laccase, peroxidase specifically catalyzes toxin decomposition. Disadvantages: free enzymes are easy to inactivate, and the reuse rate is low; the enzyme catalytic efficiency is limited by substrate specificity, and the broad-spectrum is poor. 4) composite functional materials. The closest prior art "montmorillonite-laccase composite carrier" degrades aflatoxins through physical adsorption and enzymatic degradation. Advantages: compared with single technology, the degradation rate is increased to 82%. Disadvantages: the interlayer structure of montmorillonite limits the enzyme loading capacity (≤15%); the enzyme activity half-life is <48h under high temperature and humidity environment; the preparation of composite materials requires multi-step modification, and the process is complex and the cost is high.

[0003] From the above, the current technology generally has the core problems of incomplete degradation, poor environmental adaptability, and low cost-effectiveness, especially the lack of degradation materials with broad-spectrum high efficiency, environmental stability, and industrial feasibility. SUMMARY

[0004] An object of the present application is to solve at least the above problems and to provide at least the advantages described later.

[0005] Another object of the present application is to provide a composite nanomaterial for inhibiting and degrading mycotoxins, and a preparation method and application thereof. The composite nanomaterial is used for inhibiting the growth of Aspergillus flavus, Aspergillus parasiticus or Aspergillus ochraceus, and degrading the mycotoxins produced by them, and the bacteriostatic efficiency reaches more than 95%.

[0006] In order to achieve these objects and other advantages according to the present application, a preparation method of a composite nanomaterial for inhibiting and degrading mycotoxins is provided, comprising the following steps: S1, dissolving the polyphenol component and the metal salt component in a Tris-HCl buffer solution at a molar ratio of 1:1-3, controlling the pH value of the solution to be 4-6, stirring and reacting at 20-60℃ for 1-3h to obtain a self-assembly solution, adding the activated carbon quantum dot solution drop by drop into the self-assembly solution, controlling the reaction temperature to be 25-35℃, stirring in the dark for 12-18h to obtain a reaction solution, and obtaining a precipitate after centrifugation of the reaction solution; the polyphenol component is one of tannic acid, curcumin, quercetin, and eugenol, and the metal salt component is one of copper sulfate and zinc sulfate; The preparation steps of the activated carbon quantum dot solution are as follows: 1) dissolving citric acid and ethylenediamine in deionized water at a molar ratio of 1:1.2-1.8 to form a mixed solution with a citric acid concentration of 0.1-0.3M; 2) placing the mixed solution in a water bath at 180-220℃ for 4-6h of hydrothermal reaction, cooling to room temperature, filtering the product solution through a 0.22μm filter membrane to obtain a crude solution; 3) dialyzing the crude solution through a dialysis bag with a molecular weight cut-off of 1kDa for 24h, and obtaining functionalized carbon quantum dot powder by freeze-drying of the cut-off liquid; 4) dispersing the functionalized carbon quantum dot powder in a 0.1M 2-morpholinoethanesulfonic acid buffer solution at a concentration of 10mg / mL and a pH of 6.0-7.0, adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, and activating at room temperature for 30min to obtain the activated carbon quantum dot solution; the molar ratio of the functionalized carbon quantum dot powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and N-hydroxysuccinimide is 2-3:1:1; and the mass of the functionalized carbon quantum dot powder is 8%-15% of the mass of the polyphenol component. S2, washing the precipitate with water for 3-5 times and drying to obtain the composite nanomaterial for inhibiting and degrading mycotoxins.

[0007] Preferably, in the step S1, the polyphenol component and the metal salt component are dissolved in a Tris-HCl buffer solution at a molar ratio of 1:1.2-1:2, a 0.1-0.3M sodium citrate solution is added drop by drop as a stabilizer under magnetic stirring, and the pH value of the system is controlled to be 5.0-6.0; then, dynamic reaction is carried out at an ultrasonic power of 200-400W, an ultrasonic frequency of 40kHz, and an ultrasonic temperature of 30-40℃ for 1.5-2h to enable the phenolic hydroxyl group to fully coordinate with the metal ion to obtain a self-assembly solution; and the parameters of the Tris-HCl buffer solution are as follows: 0.1mol / L, pH=8.5.

[0008] Preferably, in the S2 step, after obtaining the precipitate, the precipitate is placed in a dialysis bag with a molecular weight cut-off of 3.5 kDa, and is dynamically dialyzed with ultrapure water at 4-10°C for 24 hours, and the dialysate is replaced every 6 hours; after dialysis is completed, the liquid in the dialysis bag is obtained to obtain a suspension, the suspension is filtered through a 0.22 μm filter membrane, and then a centrifugal spray dryer is used for drying, and in the drying process, the feeding rate is controlled to be 5-10 mL / min, the inlet temperature is 85-95°C, the outlet temperature is 45-55°C, and the atomization pressure is 0.3-0.5 MPa, and finally the composite nanomaterial is obtained.

[0009] Preferably, the centrifugation mode of the reaction solution is as follows: first centrifugation at 5000 rpm for 20 min, then centrifugation at 10000-12000 rpm for 5 min, collection of the precipitate to be washed, and then the precipitate to be washed is ultrasonically washed with deionized water and anhydrous ethanol alternately for 3 times to obtain the precipitate, and each washing time is 5 min.

[0010] Preferably, the preparation step 4) of the activated carbon quantum dot solution is as follows: A1, the functionalized carbon quantum dot powder is placed in 0.1M 2-morpholinoethanesulfonic acid buffer solution with pH 6.0-7.0 at 1-4°C, and is ultrasonically dispersed at 500-800W power under ice bath conditions for 5 min to form a uniform suspension with a concentration of 10 mg / mL; A2, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride is added in three equal amounts, each addition interval is 2 min, and the molar ratio of the total amount of functionalized carbon quantum dot powder and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride is controlled to be 2.5:1; A3, after adding the last 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide is immediately injected to obtain a mixed solution; A4, the mixed solution is transferred to a sealed reactor, inert gas is introduced to replace oxygen, and the solution is continuously oscillated at 200 rpm at 25°C for 30 min, and the pH is maintained at 6.5±0.1 during the activation, and the activated carbon quantum dot solution is obtained.

[0011] The composite nanomaterial for inhibiting and degrading mycotoxins is prepared by using the preparation method of the composite nanomaterial for inhibiting and degrading mycotoxins.

[0012] The application of the composite nanomaterial for inhibiting and degrading mycotoxins is for inhibiting the growth of Aspergillus flavus, Aspergillus parasiticus or Aspergillus niger, and degrading the mycotoxins produced by Aspergillus flavus, Aspergillus parasiticus or Aspergillus niger.

[0013] The present application at least includes the following beneficial effects: The composite nanomaterial prepared from the polyphenol component and the metal salt component is used for inhibiting the growth of Aspergillus flavus, Aspergillus parasiticus or Aspergillus ochraceus and degrading the mycotoxins produced by them, and the bacteriostatic efficiency reaches more than 95%.

[0014] The composite nanomaterial is formed by the coordination of the polyphenol component (such as tannic acid, curcumin, etc.) and the metal salt component (such as copper sulfate, zinc sulfate), the phenolic hydroxyl group of the polyphenol forms a stable coordination structure with the metal ion, which gives the nanomaterial strong oxidation-reduction ability, can efficiently destroy the molecular structure of the mycotoxins (such as aflatoxin B1 and ochratoxin A), and realizes broad-spectrum degradation; at the same time, the polyphenol component and the metal salt component are both natural or biocompatible substances, and no harmful residues are produced in the degradation process, which significantly reduces the risk of environmental pollution; in addition, by flexibly adjusting the types and proportions of the polyphenol and the metal salt, the degradation requirements of different toxins can be adapted, and a general solution for the treatment of mycotoxin pollution is provided.

[0015] By limiting the specific combination of the metal salt and the polyphenol (such as copper-tannic acid, zinc-quercetin, etc.), the specific combination forms a more stable nanostructure through the molecular synergistic effect of the metal ion and the polyphenol, which significantly improves the catalytic activity and the bacteriostatic efficiency; at the same time, different combinations have selective degradation ability for specific mycotoxins (such as ochratoxin A), which enhances the targeting of the material and reduces the interference of non-target substances; in addition, after the specific component combination is determined, no additional modification steps are needed, which simplifies the preparation process, reduces the production cost, and is conducive to industrialization.

[0016] By introducing functional carbon quantum dots (CQDs), the CQDs provide abundant active sites, enhance the photocatalytic and oxidation-reduction ability of the material, and significantly improve the toxin degradation efficiency; the nanosize effect improves the dispersibility of the material in the solution, ensuring uniform and efficient reaction; at the same time, the fluorescence characteristics of the CQDs can monitor the toxin degradation process in real time, and the surface functional groups (such as amino groups) strengthen the binding ability with the toxins, realizing the integration of "degradation-detection".

[0017] By optimizing the self-assembly process (pH=4~6, 20~60℃), the beneficial effects include: precise coordination of metal ions and polyphenols under mild conditions to form uniform nanoparticles, improving the stability of the material; one-step stirring reaction instead of traditional multi-step modification process, significantly shortening the preparation time and reducing the energy consumption; Tris-HCl buffer maintains a stable pH environment, ensuring batch consistency and meeting the repeatability requirements of industrial production.

[0018] By adding sodium citrate as a stabilizer and using ultrasonic treatment, the beneficial effects include: sodium citrate inhibits particle aggregation through electrostatic repulsion, and ultrasonic cavitation promotes uniform dispersion, improving the stability of the material; ultrasonic treatment accelerates the collision frequency of molecules, significantly shortening the self-assembly time and improving the reaction efficiency.

[0019] By adopting dialysis and spray drying to purify the material, the beneficial effects are: dialysis removes unreacted substances and small molecular impurities, spray drying retains nanostructure, and high-purity product is obtained; the water content of the material after drying is low, which avoids agglomeration or inactivation during storage, significantly prolongs the shelf life; the centrifugal spray drying process supports continuous production, greatly improves the production capacity and reduces the unit cost.

[0020] By optimizing the centrifugation and washing steps, the beneficial effects include: gradient centrifugation combined with water / ethanol alternating washing completely removes free ion impurities, reduces the potential toxicity of the material; ultrasonic washing avoids mechanical damage, maintains the complete morphology and catalytic activity of the nanoparticles.

[0021] By refining the CQDs activation step (ice bath, inert gas protection), the beneficial effects are: low temperature and inert environment inhibit side reactions, optimize the activation efficiency of carboxyl groups; the amine group density of CQDs after activation is improved, which enhances the binding strength with nanomaterials and prolongs the catalytic life.

[0022] The composite nanomaterial prepared by combining metal salt components and polyphenol components is used for inhibiting fungal growth and toxin degradation, and the principle of action is: the material realizes efficient bacteriostasis by releasing metal ions to damage the fungal cell membrane, and at the same time catalyzes the degradation of the generated toxins, forming a "prevention-treatment" dual mechanism; it has broad-spectrum inhibitory effect on common toxin-producing strains such as Aspergillus flavus and Aspergillus parasiticus, reducing the risk of food contamination; the water dispersion liquid form can be directly added to agricultural products or processing links, which is convenient to operate and does not require complex equipment, and the promotion cost is low.

[0023] Other advantages, objects, and features of the present application will be apparent from the following specification, and will be appreciated by those skilled in the art. DETAILED DESCRIPTION

[0024] The present application will be further described in detail below with reference to the examples, so that those skilled in the art can implement it according to the description.

[0025] <Example 1> The present application provides a preparation method of a composite nanomaterial for inhibiting and degrading fungal toxins, which is as follows: The polyphenol component and the metal salt component are dissolved in Tris-HCl buffer solution in a molar ratio of 1:2, the pH value of the solution is controlled to be 6, the phenolic hydroxyl group is fully coordinated with the metal ion by stirring the reaction at 40 DEG C for 2h to self-assemble, to obtain a self-assembly solution; then, the self-assembly solution is centrifuged at 10000 rpm for 20 min, the precipitate is collected, washed with deionized water for 3 times, and finally dried at 50 DEG C under vacuum for 8h to obtain a composite nanomaterial; the parameters of the Tris-HCl buffer solution are: 0.1 mol / L, pH = 8.5, the polyphenol component is tannic acid, the metal salt component is copper sulfate, and the prepared composite nanomaterial is copper-tannic acid (Cu-TA).

[0026] <Example 2> Example 2 differs from example 1 in that the polyphenol component is curcumin, the metal salt component is copper sulfate, and the prepared composite nanomaterial is copper-curcumin (Cu-CUR).

[0027] <Example 3> Example 3 differs from example 1 in that the polyphenol component is quercetin, the metal salt component is copper sulfate, and the prepared composite nanomaterial is copper-quercetin (Cu-QUE).

[0028] <Example 4> Example 4 differs from example 1 in that the polyphenol component is eugenol, the metal salt component is copper sulfate, and the prepared composite nanomaterial is copper-eugenol (Cu-EUG).

[0029] <Example 5> Example 5 differs from example 1 in that the polyphenol component is tannic acid, the metal salt component is zinc sulfate, and the prepared composite nanomaterial is zinc-tannic acid (Zn-TA).

[0030] <Example 6> Example 6 differs from example 1 in that the polyphenol component is quercetin, the metal salt component is zinc sulfate, and the prepared composite nanomaterial is zinc-quercetin (Zn-QUE).

[0031] <Example 7> The application provides a preparation method of a composite nanomaterial for inhibiting and degrading mycotoxins, and specifically comprises the following steps: S0, preparation of an activated carbon quantum dot solution, specifically comprising the following steps: 1) citric acid and ethylenediamine are dissolved in deionized water in a molar ratio of 1:1.5 to form a mixed solution with a citric acid concentration of 0.2M; 2) The mixed solution is transferred to a high-pressure reaction kettle with a polytetrafluoroethylene lining, and hydrothermal reaction is carried out at 200 DEG C for 5h; after the reaction is completed, it is cooled to room temperature, and the product solution is filtered through a 0.22 mu m filter membrane to obtain a crude solution; 3) The crude solution is dialyzed through a dialysis bag with a molecular weight cut-off of 1kDa for 24h, and the cut-off liquid is freeze-dried to obtain functionalized carbon quantum dot powder; 4) The functionalized carbon quantum dot powder is dispersed in a 0.1M pH6.5 2-morpholinoethanesulfonic acid buffer at a concentration of 10mg / mL, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are added, and the mixture is activated at room temperature for 30min to obtain an activated carbon quantum dot solution; wherein the molar ratio of functionalized carbon quantum dot powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide is 2:1:1; S1, the polyphenol component and the metal salt component are dissolved in Tris-HCl buffer at a molar ratio of 1:2, the pH value of the solution is controlled to be 6, and the stirring reaction is carried out at 40 DEG C for 2h, so that the phenolic hydroxyl group is fully coordinated with the metal ion to self-assemble to obtain a self-assembly liquid; the activated functionalized carbon quantum dot solution is added dropwise into the self-assembly liquid, the reaction temperature is controlled to be 30 DEG C, and the stirring is carried out in the dark for 15h to obtain a reaction liquid, and the reaction liquid is centrifuged to obtain the precipitate; wherein the amount of the functionalized carbon quantum dot powder is 12% of the amount of the polyphenol component; the polyphenol component is tannic acid, and the metal salt component is copper sulfate; S2, the precipitate is placed in a dialysis bag with a molecular weight cut-off of 3.5kDa, and dynamic dialysis is carried out with ultrapure water at 5 DEG C for 24h, and the dialysate is replaced every 6h; after dialysis is completed, the liquid in the dialysis bag is obtained to obtain a suspension, the suspension is filtered through a 0.22 mu m filter membrane, and then a centrifugal spray dryer is used for drying, wherein the feeding rate is controlled to be 5mL / min, the inlet temperature is 90 DEG C, the outlet temperature is 50 DEG C, and the atomization pressure is 0.4MPa, and finally the composite nanomaterial is obtained.

[0032] <Example 8> The application provides a preparation method of a composite nanomaterial for inhibiting and degrading mycotoxins, and specifically comprises the following steps: S0, preparation of the activated carbon quantum dot solution, specifically comprising the following steps: 1) Citric acid and ethylenediamine are dissolved in deionized water at a molar ratio of 1:1.5 to form a mixed solution with a citric acid concentration of 0.2M; 2) The mixed solution is transferred to a high-pressure reaction kettle with a polytetrafluoroethylene lining, and hydrothermal reaction is carried out at 200 DEG C for 5h; after the reaction is completed, it is cooled to room temperature, and the product solution is filtered through a 0.22 mu m filter membrane to obtain a crude solution; 3) The crude solution is dialyzed through a dialysis bag with a molecular weight cut-off of 1 kDa for 24 h, and the cut-off liquid is freeze-dried to obtain functionalized carbon quantum dot powder; 4) The functionalized carbon quantum dot powder is dispersed in 0.1M 2-morpholinoethanesulfonic acid buffer solution at pH 6.5 at a concentration of 10 mg / mL, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are added, and the activated carbon quantum dot solution is obtained after activation at room temperature for 30 min; wherein the molar ratio of functionalized carbon quantum dot powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and N-hydroxysuccinimide is 2:1:1; S1, the polyphenol component and the metal salt component are dissolved in Tris-HCl buffer solution at a molar ratio of 1:1.5, a 0.2M sodium citrate solution is added dropwise as a stabilizer under magnetic stirring, and the pH value of the system is controlled at 5.5; then, under the conditions of ultrasonic power 300W, ultrasonic frequency 40kHz, and ultrasonic temperature 35℃, the phenolic hydroxyl group and the metal ion are fully coordinated and self-assembled for 2h to obtain a self-assembly liquid; the activated functionalized carbon quantum dot solution is added dropwise into the self-assembly liquid, the reaction temperature is controlled at 30℃, and the reaction is carried out in the dark for 15h to obtain a reaction liquid, and the precipitate is obtained after centrifugation of the reaction liquid; wherein the amount of functionalized carbon quantum dot powder is 12% of the amount of polyphenol component; the polyphenol component is tannic acid, and the metal salt component is copper sulfate; S2, the precipitate is placed in a dialysis bag with a molecular weight cut-off of 3.5kDa, and is dynamically dialyzed with ultrapure water at 5℃ for 24h, and the dialysis liquid is replaced every 6h; after dialysis, the liquid in the dialysis bag is obtained to obtain a suspension, the suspension is filtered through a 0.22μm filter membrane, and then dried by a centrifugal spray dryer; during the drying process, the feeding rate is controlled at 5mL / min, the inlet temperature is 90℃, the outlet temperature is 50℃, and the atomization pressure is 0.4MPa, and finally the composite nanomaterial is obtained.

[0033] <Embodiment 9> The application provides a preparation method of a composite nanomaterial for inhibiting and degrading mycotoxins, which specifically comprises the following steps: S0, preparation of the activated carbon quantum dot solution, specifically comprising the following steps: 1) Citric acid and ethylenediamine are dissolved in deionized water at a molar ratio of 1:1.5 to form a mixed solution with a citric acid concentration of 0.2M; 2) The mixed solution is transferred to a polytetrafluoroethylene-lined high-pressure reaction kettle, and hydrothermal reaction is carried out at 200℃ for 5h; after the reaction is completed, the product solution is cooled to room temperature and filtered through a 0.22μm filter membrane to obtain a crude solution; 3) The crude solution was dialyzed through a dialysis bag with a molecular weight cut-off of 1 kDa for 24 h, and the cut-off liquid was freeze-dried to obtain functionalized carbon quantum dot powder; 4) Preparation of activated carbon quantum dot solution, specifically comprising the following steps: A1, the functionalized carbon quantum dot powder was placed in a 0.1M pH 6.5 2-morpholinoethanesulfonic acid buffer at 2℃, and was ultrasonically dispersed at a power of 600W for 5min under ice bath conditions to form a uniform suspension; A2, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride was added in three equal amounts, with an interval of 2min each time, and the total amount of functionalized carbon quantum dot powder and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride was controlled to have a molar ratio of 2.5:1; A3, immediately after adding the last 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide was injected to obtain a mixed solution; wherein the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride to N-hydroxysuccinimide was 1:1; A4, the mixed solution was transferred to a sealed reactor, inert gas was introduced to replace oxygen, and the activation was carried out at 25℃ under continuous oscillation at 200rpm for 30min, and the pH was maintained at 6.5±0.1 during the activation, thereby obtaining the activated carbon quantum dot solution; S1, the polyphenol component and the metal salt component were dissolved in Tris-HCl buffer according to a molar ratio of 1:1.5, and a 0.2M sodium citrate solution was added dropwise as a stabilizer under magnetic stirring, and the pH value of the system was controlled to be 5.0-6.0; then, under the conditions of ultrasonic power 300W, ultrasonic frequency 40kHz, and ultrasonic temperature 40℃, the phenolic hydroxyl group and the metal ion were fully coordinated and self-assembled by dynamic reaction for 2h to obtain a self-assembly liquid; the activated functionalized carbon quantum dot solution was added dropwise into the self-assembly liquid, the reaction temperature was controlled to be 30℃, and the reaction was carried out under dark stirring for 15h to obtain a reaction liquid, and the precipitate was obtained after centrifugation of the reaction liquid; wherein the amount of the functionalized carbon quantum dot powder was 12% of the amount of the polyphenol component; the polyphenol component was tannic acid, and the metal salt component was copper sulfate; S2, the precipitate was placed in a dialysis bag with a molecular weight cut-off of 3.5kDa, and was dynamically dialyzed with ultrapure water at 5℃ for 24h, and the dialysis liquid was replaced every 6h; after dialysis, the liquid in the dialysis bag was obtained to obtain a suspension, the suspension was filtered through a 0.22μm filter membrane, and then was dried by a centrifugal spray dryer, wherein the feeding rate was controlled to be 5mL / min, the inlet temperature was 90℃, the outlet temperature was 50℃, and the atomization pressure was 0.4MPa, thereby finally obtaining the composite nanomaterial.

[0034] <Inhibition test of composite nanomaterials on mycotoxin-producing fungi> Test method: plate colony counting method, specifically as follows: 1. Materials and reagents Test fungi: Aspergillus flavus (A. flavus) Aspergillus flavus ), Aspergillus parasiticus (A. parasiticus) A. parasiticus ), Aspergillus ochraceus (A. ochraceus) A. ochraceus ); Culture medium: potato dextrose agar (PDA) Test material: 9 kinds of composite nanomaterials prepared in Examples 1-9, the prepared composite nanomaterials were dispersed in deionized water to obtain a 200 mg / L composite nanomaterial water dispersion.

[0035] 2. Experimental steps (1) Preparation of bacterial suspension: inoculate the spores of the above three Aspergillus species on PDA slant and cultivate at 28°C for 5 days; scrape the spores with sterile saline, filter (double gauze), and adjust the spore concentration to 1×10 6 CFU / mL to obtain a spore suspension.

[0036] (2) Inhibition experiment design: Experimental group: mix 200 mg / L composite nanomaterial water dispersion with the spore suspension at a volume ratio of 1:1, stand for 30 min to obtain a mixed solution; mix the composite nanomaterials of Examples 1-9 with the spore suspension to obtain mixed solutions of Examples 1-9, respectively; Control group: replace the nanomaterial solution with an equal volume of sterile water, and the rest is the same as the experimental group; (3) Plate culture and counting: take 100 μL of the mixed solution and evenly spread it on PDA plates, with 3 parallel plates for each concentration; after 48 h of cultivation at 28°C, count the number of colonies (CFU) and calculate the inhibition rate: inhibition rate = (1−experimental group CFU / control group CFU) ×100%; The specific results are shown in Table 1.

[0037] Table 1 Inhibition rate results of composite nanomaterials prepared in Examples 1-9 Experimental group Aspergillus flavus inhibition rate (%) A. parasiticus inhibition rate (%) A. ochraceus inhibition rate (%) Example 1 96.4 97.3 97.1 Example 2 96.7 97.5 98.2 Example 3 97.3 96.4 98.1 Example 4 96.8 96.3 97.2 Example 5 97.3 98.4 98.6 Example 6 98.2 97.6 97.8 Example 7 98.6 98.5 98.8 Example 8 99.5 99.8 99.3 Example 9 99.6 99.4 99.9 As can be seen from Table 1, the composite nanomaterials formed by polyphenols and metal salts, as well as the composite nanomaterials formed by polyphenols, metal salts, and functionalized carbon quantum dots can effectively inhibit the growth of Aspergillus flavus, Aspergillus parasiticus, and Aspergillus ochraceus.

[0038] <Inhibition test of composite nanomaterials on mycotoxin-producing fungi> 1. Experimental design and data acquisition Experimental group: fungal culture solution with 200 mg / L composite nanomaterials added; Control group: fungal culture solution without adding composite nanomaterials; Toxin quantification: the concentrations of aflatoxin B1 (AFB1) and ochratoxin A (OTA) were determined by HPLC.

[0039] 2. Calculation formula Toxin inhibition rate = (1 - experimental group toxin concentration / control group toxin concentration) x 100% 3. Specific steps (1) HPLC detection conditions: Column: C18 reversed-phase column (4.6 mm x 250 mm, 5 μm); Mobile phase: acetonitrile-water (60:40, v / v), flow rate 1.0 mL / min; Detector: fluorescence detector (AFB1: excitation wavelength 365 nm, emission wavelength 435 nm; OTA: excitation wavelength 333 nm, emission wavelength 460 nm).

[0040] (2) Standard curve establishment: Prepare AFB1 and OTA standard sample series concentrations; Draw the peak area-concentration standard curve and calculate the linear regression equation.

[0041] (3) Sample processing and detection: Take 1 mL of culture solution, filter through a 0.22 μm filter membrane, and then inject; According to the standard curve, calculate the toxin concentrations of the experimental group and the control group.

[0042] (4) Data statistics: Each group of experiments was repeated 3 times, and the average value was taken to calculate the inhibition rate; the specific results are shown in Table 2.

[0043] Table 2 Experimental results of the composite nanomaterials prepared in Examples 1-9 for inhibiting fungal toxins Experimental group Inhibition rate of AFB1 (%) OTA inhibition rate (%) Example 1 90.3 88.5 Example 2 91.2 89.2 Example 3 90.5 88.4 Example 4 92.2 88.6 Example 5 90.6 89.4 Example 6 91.8 90.5 Example 7 97.5 98.1 Example 8 98.8 99.1 Example 9 99.2 99.5 As can be seen from Table 2, the composite nanomaterials formed by polyphenols and metal salts, the composite nanomaterials formed by polyphenols, metal salts and functionalized carbon quantum dots can all significantly inhibit the generation of fungal toxins. At the same time, the composite nanomaterials formed by polyphenols, metal salts and functionalized carbon quantum dots have better effect on inhibiting fungal toxins than the composite nanomaterials formed by polyphenols and metal salts.

[0044] <Testing of composite nanomaterials adsorbing and degrading fungal toxins> 1. Experimental steps: Sample preparation: disperse the composite nanomaterials into a 100 mg / mL water suspension to obtain a material suspension; Toxin solution: aflatoxin B1 (AFB1) and ochratoxin A (OTA) standard solution (50 ng / mL, PBS pH 7.4) was prepared; 1) Adsorption experiment: Experimental group: 1 mL of toxin solution and 0.1 mL of 100 mg / L material suspension were taken and shaken at 25°C for 1 h; centrifugation (15,000 rpm, 10 min), HPLC detection of supernatant toxin concentration, recorded as C1.

[0045] Control group: 1 mL of toxin solution and 0.1 mL of water were taken and shaken at 25°C for 1 h; centrifugation (15,000 rpm, 10 min), HPLC detection of supernatant toxin concentration, recorded as C0.

[0046] Adsorption rate = 100% x (C0-C1) / C0; Sample: The material suspensions of Examples 1-9 were taken for adsorption experiment of experimental group, and the adsorption rates of Examples 1-9 were determined, and the results are shown in Table 3.

[0047] 2) Degradation experiment: The precipitate (i.e. the toxin-adsorbed nanomaterial) in the above adsorption experiment was gently washed twice with 1 mL of pre-cooled PBS buffer to remove a small amount of residual free toxin, and the washed precipitate was resuspended in 1 mL of fresh PBS buffer to obtain a resuspension, which was placed in a constant temperature shaker under light-free conditions and shaken at 150 rpm at 25°C for 24 hours; after the reaction was completed, 1 mL of methanol was added to the centrifuge tube, vortexed for 5 minutes, and then ultrasonicated for 10 minutes (to ensure that the nanomaterial was completely broken and all intact toxin molecules still adsorbed on its surface were extracted), and the mixture was centrifuged at 15000 rpm for 10 minutes, and the supernatant was taken. The supernatant was filtered with a 0.22 μm filter membrane, and then the toxin concentration in the filtered supernatant was detected by HPLC, recorded as C2.

[0048] Degradation rate = 100% x (C1-C2) / C1 Sample: The material suspensions of Examples 1-9 were taken for degradation experiment to determine the degradation rate, and the results are shown in Table 3.

[0049] Table 3 Adsorption experiment and degradation experiment results of composite nanomaterials prepared in Examples 1-9 Experimental group Absorption rate of AFB1 (%) AFB1 degradation rate (%) OTA adsorption rate (%) OTA degradation rate (%) Example 1 65 72 58 68 Example 2 70 85 62 78 Example 3 68 80 60 75 Example 4 72 84 65 80 Example 5 66 74 62 70 Example 6 76 82 64 74 Example 7 85 95 88 96 Example 8 88 94 89 97 Example 9 90 97 90 98 As can be seen from Table 3, the composite nanomaterials formed by the polyphenol and the metal salt and the composite nanomaterials formed by the polyphenol, the metal salt and the functionalized carbon quantum dots can significantly adsorb and degrade the mycotoxin while degrading the mycotoxin, and the composite nanomaterials formed by the polyphenol, the metal salt and the functionalized carbon quantum dots have better adsorption and degradation effects on the mycotoxin than the composite nanomaterials formed by the polyphenol and the metal salt.

[0050] 3) Photocatalytic degradation: Experimental group: 0.1 mL of 100 mg / L material suspension and 1 mL of 50 ng / mL AFB1 solution were placed under visible light (400-700 nm, 100 mW / cm2) / dark environment; sample was taken at 120 min, and the sample was immediately filtered through a 0.22 μm filter to remove the nanomaterials. 1 mL of filtrate was taken, 1 mL of methanol was added and vortexed for mixing for HPLC analysis to detect the remaining intact AFB1 concentration in the solution, denoted as Ct.

[0051] Control group: 0.1 mL of water and 1 mL of 50 ng / mL AFB1 solution were placed under visible light (400-700 nm, 100 mW / cm2) / dark environment; sample was taken at 120 min, and the sample was immediately filtered through a 0.22 μm filter. 1 mL of filtrate was taken, 1 mL of methanol was added and vortexed for mixing for HPLC analysis to detect the remaining intact AFB1 concentration in the solution, denoted as Ct0.

[0052] Degradation rate = 100% x (1-Ct / Ct0); Sample: The composite nanomaterials prepared in Examples 1, 7-9 were subjected to photocatalytic degradation experiments, and the specific results are shown in Table 4.

[0053] Table 4 Photocatalytic degradation of AFB1 by the composite nanomaterials prepared in Examples 1, 7-9 Experimental group Dark condition degradation rate (%) Degradation rate under visible light (%) Example 1 64 72 Example 7 76 89 Example 8 78 94 Example 9 82 98 As can be seen from Table 4, compared with the composite nanomaterials prepared from the metal salt and the polyphenol, the composite nanomaterials formed by the polyphenol, the metal salt and the functionalized carbon quantum dots can significantly improve the photocatalytic degradation effect, and the composite nanomaterials formed by the polyphenol, the metal salt and the functionalized carbon quantum dots have more significant improvement in the photocatalytic degradation effect than the composite nanomaterials prepared from the metal salt and the polyphenol. Overall, the composite nanomaterials formed by the polyphenol, the metal salt and the functionalized carbon quantum dots have better application prospects.

[0054] While embodiments of the application have been disclosed in connection with the above specification, it will be apparent to those skilled in the art that numerous modifications can be made thereto without departing from the overall concept of the application. Accordingly, it is intended that all such modifications be included within the scope of the claims and their equivalents.

Claims

1. A method for preparing composite nanomaterials that inhibit and degrade fungal toxins, characterized in that, Includes the following steps: S1. Dissolve the polyphenol component and the metal salt component in Tris-HCl buffer at a molar ratio of 1:1~3, control the pH of the solution to 4~6, and stir the reaction at 20~60℃ for 1~3h to obtain a self-assembled solution. Add the activated carbon quantum dot solution dropwise to the self-assembled solution, control the reaction temperature to 25~35℃, and stir in the dark for 12~18h to obtain a reaction solution. After centrifugation, obtain the precipitate from the reaction solution. The polyphenolic component is one of tannic acid, curcumin, quercetin, and eugenol, and the metal salt component is one of copper sulfate and zinc sulfate. The preparation steps of the activated carbon quantum dot solution are as follows: 1) Dissolve citric acid and ethylenediamine in deionized water at a molar ratio of 1:1.2~1.8 to form a mixed solution with a citric acid concentration of 0.1~0.3M; 2) Place the mixed solution in a hydrothermal reaction at 180~220℃ for 4~6h, cool to room temperature, and filter the product solution through a 0.22μm filter membrane to obtain a crude solution; 3) Dialyze the crude solution through a dialysis bag with a molecular weight cutoff of 1kDa for 24h, and freeze-dry the retentate to obtain functionalized carbon quantum dot powder; 4) Disperse the functionalized carbon quantum dot powder at a concentration of 10mg / mL in 0.1M... In a 2-morpholine ethanesulfonic acid buffer solution with pH 6.0–7.0, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added, and the solution was activated at room temperature for 30 min to obtain an activated carbon quantum dot solution. The molar ratio of the functionalized carbon quantum dot powder, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide was 2–3:1:1; wherein the mass of the functionalized carbon quantum dot powder was 8%–15% of the mass of the polyphenol component. S2. Wash the precipitate with water 3-5 times and dry it to obtain a composite nanomaterial that inhibits and degrades fungal toxins.

2. The method for preparing the composite nanomaterial for inhibiting and degrading mycotoxins as described in claim 1, characterized in that, In step S1: the polyphenol component and the metal salt component are dissolved in Tris-HCl buffer at a molar ratio of 1:1.2 to 1:

2. A 0.1-0.3 M sodium citrate solution is added dropwise as a stabilizer under magnetic stirring, controlling the pH of the system to 5.0-6.

0. Subsequently, the mixture is dynamically reacted for 1.5-2 hours at an ultrasonic power of 200-400 W, an ultrasonic frequency of 40 kHz, and an ultrasonic temperature of 30-40 °C, allowing the phenolic hydroxyl groups to fully coordinate and self-assemble with the metal ions, resulting in a self-assembled solution. The parameters of the Tris-HCl buffer are: 0.1 mol / L, pH = 8.

5.

3. The method for preparing the composite nanomaterial for inhibiting and degrading mycotoxins as described in claim 1, characterized in that, In step S2, after obtaining the precipitate, the precipitate is placed in a dialysis bag with a molecular weight cutoff of 3.5 kDa and dynamically dialyzed with ultrapure water at 4-10°C for 24 hours, with the dialysate being replaced every 6 hours. After dialysis, the liquid in the dialysis bag is collected to obtain a suspension. The suspension is filtered through a 0.22 μm filter membrane and then dried using a centrifugal spray dryer. During the drying process, the feed rate is controlled at 5-10 mL / min, the inlet temperature at 85-95°C, the outlet temperature at 45-55°C, and the atomization pressure at 0.3-0.5 MPa, finally obtaining the composite nanomaterial.

4. The method for preparing the composite nanomaterial for inhibiting and degrading mycotoxins as described in claim 1, characterized in that, The reaction solution is centrifuged as follows: first, centrifuge at 5000 rpm for 20 min, then centrifuge at 10000~12000 rpm for 5 min, collect the precipitate to be washed, and then wash the precipitate with deionized water and anhydrous ethanol alternately three times by ultrasonication to obtain the precipitate, each time for 5 min.

5. The method for preparing the composite nanomaterial for inhibiting and degrading mycotoxins as described in claim 1, characterized in that, Step 4) of preparing the activated carbon quantum dot solution is as follows: A1. Place the functionalized carbon quantum dot powder in a 0.1M pH 6.0-7.0 2-morpholine ethanesulfonic acid buffer solution at 1-4℃, and ultrasonically disperse it for 5 min at 500-800W power under ice bath conditions to form a uniform suspension with a concentration of 10mg / mL. A2. Add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride in three equal portions, with a 2-minute interval between each addition, and control the molar ratio of the total amount of functionalized carbon quantum dot powder to 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride to be 2.5:

1. A3. Immediately after adding the last 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide is injected to obtain a mixture; A4. Transfer the mixture to a closed reactor, introduce inert gas to replace oxygen, and continuously oscillate at 200 rpm at 25°C for 30 min. Maintain pH=6.5±0.1 during the activation process to obtain the activated carbon quantum dot solution.

6. A composite nanomaterial for inhibiting and degrading fungal toxins, characterized in that, It was prepared using the method for preparing composite nanomaterials that inhibit and degrade fungal toxins as described in any one of claims 1 to 5.

7. The application of the composite nanomaterial for inhibiting and degrading mycotoxins as described in claim 6, characterized in that, It is used to inhibit the growth of Aspergillus flavus, Aspergillus parasiticus, or Aspergillus ochraceus, and to degrade the fungal toxins produced by Aspergillus flavus, Aspergillus parasiticus, or Aspergillus ochraceus.